AI-Generated code detection: an examination of current tools in education (2025)
This document explores the challenge of detecting AI-generated Python code in education, highlighting limitations of current detection tools, especially against simple obfuscation techniques. It emphasizes the need for advanced, resilient detection methods and ethical AI use in academic settings.